Differences in Students’ Physical Self-Perception in PE Classes According to Gender and Nutritional Status - Donata Vidaković Samaržija; Lara Pavlić; Jelena Alić (Journal of Elementary Education, 2023)
The purpose of the study was to examine the level of physical self-perception (PSP) in the Physical Education class, and to determine differences in dimensions of PSP according to gender and nutritional status. On a sample of 283 4th- and 8th-graders in primary school, an anonymous questionnaire was applied. Fourth-graders made higher assessments of their coordination, sport competences, strength, flexibility and endurance than 8th graders. Moreover, significant differences were obtained in certain dimensions of PSP with regard to gender and nutritional status. A low level of PSP may be an obstacle to physical activity. These results indicate that PSP decreases by age and by gender.